Abundance and seasonal diversity of zooplankton in coastal aquatic environments of Mathbaria, Bangladesh (Dhaka University Journal of Biological Sciences, 2011)
Monthly seasonal diversity and abundance of zooplankton species at three ponds of Mathbaria were investigated from surface water column during January 2008 to December 2008. Thirty?six species of zooplankton were identified from the ponds. Among these, 25 belonged to rotifer, six were of protozoan, three were copepods and one each from cladocera and ostracoda. Nauplii (copepods) were the most abundant (39.09% in site 1, 36.81% in site 2, and 33.06% in site 3) group, while the ostracoda were the least abundant (0.1% in site 2) group. The relative abundance was maximum (39.09%) for nauplii and minimum (4.56%) for cladocera in site 1; maximum (36.81%) for nauplii and minimum (0.1%) for ostracoda in site 2; maximum (33.15%) for rotifer and minimum (1.17%) for Cladocera in site 3. The species of frequent occurrence (100%) were Cyclops sp. and copepoda nauplius. In Bangladesh, cholera outbreaks have two major peaks, one between March to May and other between August to October. This study shows that, seasonal diversity and abundance of zooplankton species varied with seasons, the zooplankton peaks coincide to the reported peak outbreak of cholera at the area. Key words: Seasonal diversity; Mathbaria; Zooplankton; Abundance DOI: http://dx.doi.org/10.3329/dujbs.v20i2.8977 DUJBS 2011; 20(2): 163-171